Recessive lethal mutations resulting from deletion of closely linked loci in balanced heterokaryons of Neurospora crassa - F. J. de Serres; B. B. Webber (Fungal Genetics Reports, 1963)
Recessive lethal mutations resulting from deletion of closely linked loci in balanced heterokaryons of Neurospora crassa